The interaction between gut microbiota and periodontal health: a new paradigm in periodontal diseases (Research, Society and Development, 2025)
The understanding of human health has advanced toward an increasingly integrated perspective that recognizes the interaction among different body systems. In this context, the relationship between gut microbiota and periodontal health stands out as a promising field in Dentistry. The present study aimed to investigate the influence of gut microbiota on periodontitis. To this end, an integrative literature review was conducted using the PubMed via Medline, PubMed Central, Scielo, and LILACS databases, including full-text, peer-reviewed articles published between 2021 and 2025 in Portuguese and English. After the screening process, 11 studies met the eligibility criteria and were qualitatively analyzed. The results demonstrated that oral and intestinal dysbiosis establish a feedback relationship, promoting persistent inflammatory processes that compromise systemic homeostasis. Different microbial translocation pathways were identified—enteral, hematogenous, and host cell-mediated—with Porphyromonas gingivalis being one of the main agents associated with the disruption of the intestinal barrier. Furthermore, adjunctive strategies such as the use of probiotics proved promising in restoring microbial balance and controlling periodontal inflammation. It is concluded that periodontitis should be understood not only as a locally manifested disease but as part of a broader systemic process. This perspective reinforces the importance of integrated therapeutic approaches and the need for new clinical trials to consolidate the role of the gut–oral axis in dental practice.